2017
DOI: 10.1021/acs.est.7b02008
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Anthropogenic Factors to Freely Dissolved Polycyclic Aromatic Hydrocarbons in Freshwater of China

Abstract: Assessment of surface water pollution by organic pollutants is a top priority in many parts of the world, as it provides critical information for implementing effective measures to ensure drinking water safety. This is particularly important in China, where insufficient data of national scale have been acquired on the occurrence of any organic pollutants in the country's water bodies. To fill the knowledge gap, we employed passive samplers to survey polycyclic aromatic hydrocarbons (PAHs) in 42 freshwaters thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 53 publications
(93 reference statements)
0
26
0
Order By: Relevance
“…The cluster in 2010 was positive on PC1, while the cluster in 2015 was negative on PC1. PAHs with higher rings were supposed to be mainly originated from fuel combustions at industrial temperature and domestic coals, and those with low rings were probably originated from combustion of transport petroleum . Therefore, the PCA result for individual PAH concentrations in different years also confirmed that the emissions of PAHs were decreased from industrial petroleum, industrial, coking, and domestic coal sources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cluster in 2010 was positive on PC1, while the cluster in 2015 was negative on PC1. PAHs with higher rings were supposed to be mainly originated from fuel combustions at industrial temperature and domestic coals, and those with low rings were probably originated from combustion of transport petroleum . Therefore, the PCA result for individual PAH concentrations in different years also confirmed that the emissions of PAHs were decreased from industrial petroleum, industrial, coking, and domestic coal sources.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the reduction of the airborne PAHs and other air pollutants benefited from the energy transition policy in northern China. Recent research found that, in an aqueous environment, PAH concentrations were highly dependent on anthropogenic factors, such as population density, economic development, and urbanization. , In the Rhine and Elbe Rivers, Germany, the loads of PAHs absorbed on suspended particulate matter decreased due to the substitution of coal and petroleum with renewable energies . Urban rivers in Beijing are typical for arid regions, whose principal water source was WWTP effluent, different from natural rivers.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) refer to a group of compounds with two or more benzene rings that are linked to form large conjugated systems with high fat solubility and relatively low water solubility [1]. PAHs have attracted worldwide attention due to their high toxicity, serious carcinogenic properties and refractory degradation [2].…”
Section: Introductionmentioning
confidence: 99%
“…PAHs have attracted worldwide attention due to their high toxicity, serious carcinogenic properties and refractory degradation [2]. The US Environmental Protection Agency (EPA) recognized 16 PAHs as priority pollutants [1]. Biochemical treatment is regarded as one of the most promising technologies to remove PAHs in aqueous environment due to its low operating cost, however, PAHs tend to retain their conjugated ring systems when they react because of their stable chemical properties and low bioavailability [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The typical 3-ring PAHs of acenaphthene (ACE), acenaphthylene (ACY), fluorene (FLU) and 4-ring PAHs of fluoranthene (FLT) and pyrene (PYR) were selected as the target PAHs. All of the five PAHs have high water quality guidelines that were developed by the U.S. Environmental Protection Agency (EPA) [22]. The specific objectives of this study are to: 1) evaluate the influence of mussels on the purification of five PAHs in CWs; 2) evaluate the influence of these five PAHs on standard water quality variables (COD, NO 3 -N, ammonium (NH 4 -N), total nitrogen (TN)); and 3) determine the contributions of CWs components (plants, substrate, and others) and their relationship to the removal of the five PAHs under the influence of mussels.…”
Section: Introductionmentioning
confidence: 99%